Distribution of fungi in a Triassic fern stem. (30th October 2018) - Harper, Carla J.; Galtier, Jean; Taylor, Thomas N.; Taylor, Edith L.; Rößler, Ronny; Krings, Michael
ABSTRACT: Documented evidence of fungi associated with Mesozoic ferns is exceedingly rare. Three different types of fungal remains occur in a portion of a small, permineralised fern stem of uncertain systematic affinities from the Triassic of Germany. Exquisite preservation of all internal tissues made it possible to map the spatial distribution of the fungi in several longitudinal and transverse sections. Narrow, intracellular hyphae extend through the entire cortex, while wide hyphae are concentrated in the cortical intercellular system adjacent to the stele and leaf traces. Hyphal swellings occur in the phloem and adjacent cortex, while moniliform hyphae (or chains of conidia) are present exclusively in parenchyma adjacent to the stele. No host response is recognisable, but host tissue preservation suggests that the fern was alive during fungal colonisation. The highest concentration of fungal remains occurs close to the stele and leaf traces, suggesting that the fungi either utilised the vascular tissues as an infection/colonisation pathway or extracted nutrients from these tissues. This study presents the first depiction of fungal distribution throughout a larger portion of a fossil plant. Although distribution maps are useful tools in assessing fungal associations in relatively small, fossil plants, preparing similar maps for larger and more complex fossils would certainly be difficult and extremely arduous.